Additive Manufacturing Technologies Rapid Prototyping to Direct Digital Manufacturing - Gibson, Ian.; Rosen, David W.; Stucker, Brent; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Additive Manufacturing Technologies: Rapid Prototyping to Direct Digital Manufacturing deals with various aspects of joining materials to form parts. Additive Manufacturing (AM) is an automated technique for direct conversion of 3D CAD data into physical objects using a variety of approaches. Manufacturers have been using these technologies in order to reduce development cycle times and get their products to the market quicker, more cost effectively, and with added value due to the incorporation of customizable features. Realizing the potential of AM applications, a large number of processes have been developed allowing the use of various materials ranging from plastics to metals for product development. Authors Ian Gibson, David W. Rosen and Brent Stucker explain these issues, as well as: Providing a comprehensive overview of AM technologies plus descriptions of support technologies like software systems and post-processing approaches Discussing the wide variety of new and emerging applications like micro-scale AM, medical applications, direct write electronics and Direct Digital Manufacturing of end-use components Introducing systematic solutions for process selection and design for AM Additive Manufacturing Technologies: Rapid Prototyping to Direct Digital Manufacturing is the perfect book for researchers, students, practicing engineers, entrepreneurs, and manufacturing industry professionals interested in additive manufacturing. .
and Basic Principles -- Development of Additive Manufacturing Technology -- Generalized Additive Manufacturing Process Chain -- Photopolymerization Processes -- Powder Bed Fusion Processes -- Extrusion-Based Systems -- Printing Processes -- Sheet Lamination Processes -- Beam Deposition Processes -- Direct Write Technologies -- Design for Additive Manufacturing -- Guidelines for Process Selection -- Software Issues for Additive Manufacturing -- Direct Digital Manufacturing -- Medical Applications for Additive Manufacture -- Post-Processing -- The Use of Multiple Materials in Additive Manufacturing -- Business Opportunities and Future Directions.
Keywords: Engineering design; Chemical engineering; Industrial engineering; Production engineering; Mechanical engineering; Manufactures; Engineering Design; Industrial Chemistry/Chemical Engineering; Industrial and Production Engineering; Mechanical Engineering; Manufacturing, Machines, Tools, Processes